Dataset for AABS baseline/characterization in Kenya (wp1) - Manyise, Timothy; Brako Dompreh, Eric (2024)
This study was conducted to understand the use of digital systems in the coastal fisheries sector of Kenya. This study is part of a new project called the Asia Africa Bluetech Superhighway (AABS), which aims to scale digital tools for fisheries management in Kenya. Primary data was collected from 2137 fisherfolk and 319 traders across 4 counties in October 2024. A structured questionnaire was developed and deployed on the KoboToolbox platform, facilitating efficient data collection through mobile tablets. The dataset recorded demographics, fishing activities, cost and revenues, market dynamics, fisheries management, knowledge, access and use of digital tools, access to weather forecast, climate and environment, food and nutrition security, gender, decision making and women empowerment, and poverty.